Comparative aesthetics: Indian and Western - Mukherji, Ramaranjan (Calcutta : Sanskrit Pustak Bhandar, 1991)
Study with special reference to Sanskrit literature.
Includes bibliographical references (p. [156]-161).
Keywords: Sanskrit literature -- History and criticism; Aesthetics, Comparative